Return-to-play criteria following sports injury - Clover, J.; Wall, J. (Clinics in Sports Medicine, 2010)
Determining the criteria for an injured athlete's return to competition can be a confusing scenario when all the individuals involved are brought in. These may include the athlete, parents, guardians, coaches, family physician, the athletic trainer, and others. Providing a foundation from which all can understand the reasoning is key. It must be understood that the primary responsibility is to cause no harm to the athlete, while enabling him or her to participate at the highest level possible. This article discusses the importance of establishing guidelines, athletes' behavioral responses to RTP decisions, testing procedures, and the level of sport and intangible factors related to RTP criteria.